Classification of Solar Plasma Flows by Analyzing Out- and Intra-Magnetospheric Magnetohydrodynamic Oscillations During Magnetic Storms - A. Barkhatov, N.; E. Revunov, S.; M. Barkhatova, O.; A. Revunova, E.; S. Dolgova, D.; A. Glavatsky, Yu. (International Journal of Engineering and Technology, 2018)
Comparison of wavelet spectrum (skeletons) local maxima for disturbed components of solar plasma flow parameters and geomagnetic field disturbances recorded along the meridional station chain during geomagnetic storm intervals is performed in the range of magnetohydrodynamic (MHD) waves. An algorithm for quantitative evaluation of analyzed skeletons consistency has been developed. It has been used to demonstrate the possibility of the type of solar wind plasma flow elaboration on unique spectral signs of Solar wind speed disturbances, density and interplanetary magnetic field. It is shown that the energy spectrum of oscillations for these parameters reflects the internal structure of the corresponding plasma formation. The skeletons application to the analysis of the interplanetary space main parameters made it possible to estimate the magnetosphere reaction time in geomagnetic field horizontal component oscillations at different latitudes on the disturbance. As a result, the distributed magnetosphere reaction over latitude was determined in the form of geomagnetic field oscillations on the disturbed solar flow parameters. It is shown that the dynamics of the components of the solar wind parameters disturbance spectra corresponding to plasma flows manifest themselves in the MHD spectra of high-latitude stations magnetograms and can be used as a diagnostic tool.Â Â